ANALISIS DAN IMPLEMENTASI TEKNOLOGI ADAPTIVE BITRATE STREAMING TERHADAP KONDISI BANDWIDTH (Studi Kasus : Valu TV (PT Distribusi Media Teknologi)) - Iindra Iriyanti; Arini Arini; Defiana Arnaldy (PETIR, 2015)
The growth of the internet and smart device users in Indonesia is quite rapidly and is expectedto continue to increase each year . Internet users in Indonesia come from various backgrounds andages . It is often done internet users are watching streaming video via their smart devices . Moreand more users are accessing internet streaming video it will affect the condition of the bandwidthprovided by the ISP ( Internet Service Provider ) which would affect the user experience due tobuffer the video stream when the video is being watched . Looking at these problems , a companyengaged in the field of streaming TV ( PT Distribution Media Technology ) setting up a streaming TVservice using a technology that is relatively new in Indonesia , namely Adaptive Bitrate Streamingtechnology that can solve the problems of the video stream buffer . Knowing that the AdaptiveBitrate Streaming technology is relatively new in Indonesia , the researchers tried to analyze theAdaptive Bitrate Streaming technology as well as the influence of bandwidth conditions for thesetechnologies . In this study , researchers used a quantitative method to analyze the Adaptive BitrateStreaming technology , implement the technology on several devices and analyze the effect ofbandwidth on facility conditions VOD ( Video on Demand ) which is implemented using AdaptiveBitrate Streaming technology that existed at Valu TV service ( PT Distribution Media Technology ) .The results of this analysis is to find out how to work the Adaptive Bitrate Streaming technology andits implementation on bandwidth conditions while riding , stable , and down . With the AdaptiveBitrate Streaming technology , users can watch a video streaming video comfortably without bufferdespite their internet bandwidth conditions are unstable.